Virtual Screening of Flavonoid Compounds as A Main Protease Inhibitor for Anti-Sars-Cov-2 Candidates - Saeful Amin; Fadhilah Utami; Selvira Anandia Intan Maulidya (Indonesian Journal of Pharmaceutical Science and Technology, 2022)
In 2019, the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) was discovered in Hubei Province, China. After one year, no drug therapy has been approved, necessitating the development of SARS-CoV-2 drugs. To screen new drug candidates from natural product databases, the in-silico method, a drug discovery process based on computer simulations, can be utilized. Flavonoid is one of the most common compounds found in nature. They are secondary metabolites compounds contains phenolic functional group that can be virtually screened by predicting antiviral activity, drug likeness prediction, pharmacokinetic prediction, toxicity prediction, and molecular docking simulation Virtual screening is used in molecular docking simulations to design drugs based on activity prediction, compound similarity with oral drugs based on similar physical properties, pharmacokinetic profiles that include absorption and distribution, toxicity, and interactions of compounds with targets. The main protease used by target receptors is an enzyme that is important in determining SARS-CoV-2 survival. The structure of SARS-CoV-2 main protease code ID PDB 5RL4, 5R7Y and 7BUY is used in molecular docking simulation. The results of virtual screening of 80 flavonoid compounds showed that there are two most potential compounds, namely naringin and rutin that have lower ∆G values than the three native ligands, predictions of toxicity and good activity and a fairly good distribution profile.